(Inter)regional Input-Output Table Estimation from Surveys to Spatial Econometrics - Torój, Andrzej (Central European Journal of Economic Modelling and Econometrics, 2025)
Researchers and practitioners who consider economic regional (sub-national) policy questions often face the problem of regional input-output (I–O) table unavailability. The literature offers a number of approaches to approximate such tables. In this paper, a survey of the leading state-of-the-art methods in the field is presented, and their pros and cons are discussed. I take into account both single-region approaches, such as the location quotient (LQ) family, as well as interregional input–output (IRIO) methods, especially their class referred to as gravity-RAS. I pay particular attention to recent developments in using spatial econometric methods (Spatial IRIO). The discussion is illustrated with simple numerical examples and selected empirical results.